Monitoring of gene expression in tacrolimus-treated de novo renal allograft recipients facilitates individualized immunosuppression: results of the IMAGEN study - Sommerer, Claudia; Brunet, Mercè; Budde, Klemens; Millán, Olga; Guirado Perich, Lluis; Glander, Petra; Meuer, Stefan; Zeier, Martin; Giese, Thomas (British journal of clinical pharmacology, 2021)
AIMS: Calcineurin inhibitors (CNI) have a small therapeutic window, and drug monitoring is required. Pharmacokinetic monitoring does not correlate sufficiently with clinical outcome. Therefore, the expression of nuclear factor of activated T cells (NFAT)-regulated genes in the peripheral blood has been suggested as a potentially useful immune monitoring tool to optimize CNI therapy. NFAT-regulated gene expression (RGE) was evaluated in renal allograft recipients as predictive biomarker to detect patients at risk of acute rejection or infections. METHODS: NFAT-RGE (interleukin-2, interferon-γ, granular-macrophage colony-stimulating factor) was evaluated by quantitative real-time polymerase chain reaction in whole blood samples at day 7, day 14, month 1, 3, and 6 after transplantation in 64 de novo renal allograft recipients from 3 European centres. Immunosuppression consisted of tacrolimus (Tac), mycophenolic acid, and corticosteroids. RESULTS: Tac concentrations (C0 and C1.5) correlated inversely with NFAT-RGE (P < .01). NFAT-RGE showed a high interindividual variability (1-61%). Patients with high residual gene expression (NFAT-RGE ≥30%) were at the increased risk of acute rejection in the following months (35 vs. 5%, P = .02), whereas patients with low residual gene expression (NFAT-RGE <30%) showed a higher incidence of viral complications, especially cytomegalovirus and BK virus replication (52.5 vs. 10%, P = .01). CONCLUSIONS: NFAT-RGE was confirmed as a potential noninvasive early predictive biomarker in the immediate post-transplant period to detect patients at risk of acute rejection and infectious complications in Tac-treated renal allograft recipients. Monitoring of NFAT-RGE may provide additional useful information for physicians to achieve individualized Tac treatment.